Wave Transmission and Reflection of the Alternatively Submerged Geotube Breakwater - Saadon, Muhammad Syukri (IRC, 2016)
This paper conducted the experiment on investigating the effect of wave on transmission and reflection of the alternatively submerged geotextile tubes breakwater when subjected to regular waves. Hydraulic characteristics of modular of alternatively submerged geotube such as wave steepness Hi/L, relative wave height Hi/d, and relative submergence, d’/Hi are being determined in order to achieve the aim at the end of the process. From the research gap of other research, the project study about designing and the application of geotextile tube structure in providing a natural barrier at coastal areas.